(untitled) (Revista de Estudos da Linguagem, 2003)
The aim of this paper is to describe some of the linguistic andstrategic means used for the construction of social relations by theparticipants of face to face interactions. Based on the notion offacework introduced by GOFFMAN (1967), we have analyzed theinteractional moves of 12 members of a social subgroup in aBrazilian speech community when asked to express their views ona few polemical topics in individual and group interview situations.Having in mind that the blend of such interactional moves mightlead to the overriding line of conduct adopted, we have set out todescribe the interactional function of the linguistic andconversational strategies in which these moves seem to be partlyencoded. The strategies focused on here are the ones whose socialmeaning contributes to what GOFFMAN (1967) called “aggressiveuse of facework”, here referred to as Agonism.